2020
DOI: 10.1093/ejcts/ezaa009
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve repair with a newly approved geometric annuloplasty ring in patients undergoing proximal aortic repair: early results from a single-centre experience

Abstract: OBJECTIVES Aortic insufficiency (AI) is common in patients with proximal aortic disease, but limited options exist to facilitate aortic valve repair (AVr) in this population. This study reports ‘real-world’ early results of AVr using newly FDA-approved trileaflet and bicuspid geometric annuloplasty rings for patients with AI undergoing proximal aortic repair (PAR) in a single referral centre. METHODS All patients undergoing A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…In‐hospital mortality was zero and postoperative morbidity rates were remarkably low 9 . Similar results were also extracted by the largest American series concerning HAART rings 1 . Among 47 patients who received the internal geometric annuloplasty ring along with ascending aorta/aortic root replacement, 30‐day/in‐hospital mortality was zero.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In‐hospital mortality was zero and postoperative morbidity rates were remarkably low 9 . Similar results were also extracted by the largest American series concerning HAART rings 1 . Among 47 patients who received the internal geometric annuloplasty ring along with ascending aorta/aortic root replacement, 30‐day/in‐hospital mortality was zero.…”
Section: Discussionsupporting
confidence: 67%
“…Among 32 patients whose imaging was available at last follow‐up, zero AI was detected in 47%, 1+ AI in 50% and 2+ AI in 3%. Interestingly, none of the eight patients, who received a valve sparing root replacement procedure along with HAART subannular implantation having less than 2+ preoperative AI, had more than 1+ AI at last follow‐up 1 . Another large, multicenter, European trial by Rankin et al 12 also reported promising results of internal geometric ring annuloplasty along with intervention in the proximal aorta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The early clinical results of aortic ring annuloplasty as an adjunct to AVr have been presented elsewhere. 12,13,17 -20 At this point in time, approximately 1,000 rings have been implanted clinically for 40 different AI pathologies, with an AI repair rate exceeding 90%. 11 Long-term follow-up data are becoming available and demonstrate an 8-year Kaplan-Meier freedom from all-cause death and reoperation exceeding 80%, 21 consistent with other repair outcomes.…”
Section: Discussionmentioning
confidence: 99%